Maternal Flt-1 and endoglin expression by circulating monocyte subtype and polarization in preeclampsia and fetal growth restriction - Thushari Indika Alahakoon; Heather Medbury; Helen Williams; Nicole Fewings; Xin Wang; Vincent Lee (Elsevier, 2019)
Objective: Circulating levels of the anti-angiogenic factors sFlt-1 and sEndoglin are elevated in preeclampsia (PE) and fetal growth restriction (FGR), mainly secreted from placental trophoblast. This study aims to identify the contributory role of monocyte Flt-1 and endoglin expression in PE and FGR. Study design: A prospective cross-sectional study was conducted and patients recruited from four clinical groups including normal pregnancy, PE, FGR and PE + FGR. Peripheral blood samples and cord blood were collected from 54 pregnant women between 24-40 weeks of gestation. Monocyte subset distribution was assessed using CD14 and CD16 expression and the surface expression of Flt-1, endoglin, CD86 and CD163 assessed by flow cytometry. We compared these factors between (1) clinical groups. (2) monocyte subset (3) monocyte polarization and (4) gestational age. Results: Across all clinical groups, Flt-1 was mainly expressed by classical and intermediate monocytes, but no differences between clinical groups were observed. Surface expression of endoglin was higher on intermediate and non-classical monocytes and decreased in PE + FGR total monocytes. Flt-1 and endoglin expression correlated with increasing gestational age as well as higher CD86/CD163 ratio favouring M1 polarisation. The fetal monocyte endoglin expression was increased in FGR. Conclusion: We conclude that monocyte Flt-1 and endoglin expression increase with gestational age and with M1 polarization suggesting their upregulation with inflammatory changes in monocytes. Endoglin expression by M1 monocytes may play a part in increased cardiovascular risk associated with preeclampsia. Endoglin expression on fetal monocytes is increased in FGR as a likely response to placental injury. Keywords: Pregnancy, Preeclampsia, Fetal growth restriction, Monocyte, Subsets, Endoglin, Fms like tyrosine kinase inhibitor